The Effectiveness of Systemic Family Therapy on Alexithymia, Psychological Capital, and Mental Vitality in Mothers Infected with COVID-19 with Autistic Children - Razmkhah, Nasim; Jafar Tabatabaei, Samaneh Sadat; Nasri, Mayram; Shahbazizadeh, Fatemeh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The objective of the present study was to compare the effectiveness of systemic family therapy in reducing alexithymia, increasing psychological capital, and enhancing mental vitality in mothers infected with COVID-19 who have autistic children.Methods: The research method was a quasi-experimental design utilizing a pretest-posttest and follow-up with a control group. The statistical population included mothers infected with COVID-19 who have autistic children in the city of Mashhad, referring to the Avaye Salamat Center (total number: 70 individuals). Data were collected using a cluster random sampling method, ultimately selecting 30 individuals and assigning them into two groups of 15 each, experimental and control. For data collection and assessment of desired features and conditions, demographic forms and marital intimacy, forgiveness, and marital burnout questionnaires were used. Participants in the experimental group underwent systemic family therapy according to Bowen's (2009) protocol in 8 sessions of 90 minutes each, twice a week. Data analysis was conducted using repeated measures analysis of variance and SPSS-16 statistical software.Findings: The results indicated that systemic family therapy significantly reduced alexithymia (F=6.25, P=0.004), increased psychological capital (F=9.65, P=0.001), and enhanced mental vitality (F=7.29, P=0.001) in mothers infected with COVID-19 who have autistic children (P